Flow Field Analysis of Adult High-Flow Nasal Cannula Oxygen Therapy. (22nd July 2021) - Xia, Jingen; Chang, Jiaqi; Liang, Jixiang; Wang, Yixuan; Wang, Na
Abstract : The mechanical ventilation of human body is a complex human-computer interaction process. High flow nasal cannula oxygen therapy (HFNC) is a new type of ventilation, which is often measured by lung pressure, respiratory work, and other parameters. The purpose of this paper is to analyse the pressure, flow, and strain rate of upper respiratory tract with different flow and oxygen concentration by using finite element simulation, to guide professionals to adjust the appropriate flow and oxygen concentration parameters of HFNC machine. This paper studies the complex human-computer interaction environment of human respiratory tract and ventilation airflow. The 3D model of respiratory tract established by the conversion of image scanning data was taken as the research object. The flow state of the gases in the respiratory tract was judged by Reynolds equation. After that, RNG K- ε model was applied to the research object, and the simulation diagram of airway pressure, flow rate, strain rate, and trace diagram of flowing particles were obtained under the finite element method. The results explain some clinical phenomena in HFNC and guide people to make better use of mathematical tools to study human-computer complex environment.